2021
DOI: 10.1210/clinem/dgab275
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Hyperandrogenism and Response to Gonadotropin-releasing Hormone Analogues in Primary Severe Insulin Resistance

Abstract: Context Insulin resistance (IR) is associated with polycystic ovaries and hyperandrogenism, but underpinning mechanisms are poorly understood and therapeutic options are limited. Objective To characterize hyperandrogenemia and ovarian pathology in primary severe IR (SIR), using IR of defined molecular etiology to interrogate disease mechanism. To extend evaluation of gonadotropin-releasing hormone (GnRH) analogue therapy in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
2
17
1
Order By: Relevance
“…The major insulin resistance observed in patient 1 might thus contribute to hyperandrogenism signs. Nevertheless, her total testosterone levels are much higher than those usually observed in lipodystrophic patients ( Huang-Doran et al, 2021 ). Such an elevation of testosterone levels in the absence of tumor and in the presence of normal estradiol levels rather argue for a direct or indirect blockade of the aromatase activity.…”
Section: Discussioncontrasting
confidence: 57%
“…The major insulin resistance observed in patient 1 might thus contribute to hyperandrogenism signs. Nevertheless, her total testosterone levels are much higher than those usually observed in lipodystrophic patients ( Huang-Doran et al, 2021 ). Such an elevation of testosterone levels in the absence of tumor and in the presence of normal estradiol levels rather argue for a direct or indirect blockade of the aromatase activity.…”
Section: Discussioncontrasting
confidence: 57%
“…Challenging this notion, administration of testosterone as part of a gender affirming hormone therapy to female‐to‐male transgender individuals does not promote insulin resistance or a metabolic phenotype 60 . Additionally, genetic causes of extreme insulin resistance in women result in high circulating testosterone, suggesting that hyperinsulinaemia promotes hyperandrogenism, not necessarily the reverse 61 . In any case, female hyperandrogenism is associated with both blunting negative feedback control of the HPG axis, as well as clamping down HPG axis output.…”
Section: Discussionmentioning
confidence: 99%
“…60 Additionally, genetic causes of extreme insulin resistance in women result in high circulating testosterone, suggesting that hyperinsulinaemia promotes hyperandrogenism, not necessarily the reverse. 61 In any case, female hyperandrogenism is associated with both blunting negative feedback control of the HPG axis, as well as clamping down HPG axis output. The outcome may be dependent upon the developmental window of first exposure, the relative level of the androgen exposure, and the aromatisable nature of the elevated androgen.…”
Section: Ta B L Ementioning
confidence: 99%
“…PCOS is a major cause of subfertility ( Goodarzi et al, 2011 ) and features increased ovarian volume and histological abnormalities, including hyperplasia of thecal cells and dyscoordinated follicular maturation ( Jonard et al, 2007 ). Observations of people with single-gene causes of IR, or reversible severe IR due to INSR-blocking autoantibodies, establish that primary IR is sufficient to induce changes indistinguishable from PCOS, as long as secretion of gonadotrophin hormones from the pituitary gland is intact ( Huang-Doran et al, 2021 ).…”
Section: Ir or Insulin Action Imbalance?mentioning
confidence: 99%
“…Some ex vivo studies of primary cells from patients suggested that a selective defect in ‘metabolic signalling’ via PI3K might explain excessive ovarian growth in the context of PCOS or pseudoacromegaly ( Flier et al, 1993 ; Dib et al, 1998 ; Book and Dunaif, 1999 ; Corbould et al, 2006 ). However, people with primary defects impairing INSR function often have very-severe PCOS, arguing against this ( Huang-Doran et al, 2021 ; Huang-Doran et al, 2016 ). Indeed, the notion that insulin exerts ‘metabolic’ effects via PI3K and ‘mitogenic’ effects mostly via RAS/RAF/MEK/ERK sits uneasily with the overgrowth caused by selective genetic activation of PI3K, and with the demonstrated crosstalk between the pathways ( Madsen et al, 2018 ; Castellano and Downward, 2011 ).…”
Section: How Does a Compensatory Increase In Insulin Cause Disease?mentioning
confidence: 99%